GRAFENO POROSO NITROGENADO (C2N-H2D): UM EXCELENTE SENSOR DE AMINOACIDOS NEUROTRANSMISSORES - SOUSA, Giovando Marques de (2022)
Studying the physical-chemical interactions between biomolecules and two-dimensional carbon-based structures can assist in the development and characterization of new biossensors. The controlled manipulation of each component is related to the construction of receptors or sensors what show biomolecules structures with different conformations and consequently dif ferente electronic properties. In this work, we study the structural and electronic properties of different adsorbed neurotransmitters amino acids on one two-dimensional layer (2D) of nitro genated holey graphene (C2N-h2D). The neurotransmitters are present in synaptic events and carry informations to outhers cels performing thus a function of biosignaling. The amino acids such as: γ-aminobutyric acid (Gaba) and and Glycine are important inhibitory neurotransmitters of the central nervous system of mammals, and perform an important role in regulating neuronal excitability throughout the nervous system. Glutamate, in turn, is an excitatory neurotransmitter of the nervous system, being the most common in mammals. The decrease of these substances, as well as of others NAAs, induces psychiatric and neurological diseases. Thus, the detection and quantifal of these molecules are important for the rapid diagnosis of these dysfunctions. Based-carbon nanostructured materials have been used in the study and development of devi ces capable of mapping molecular biosensing. However, recent results have been showed a high toxicity of these materials when interact with structural amino acids. In recent works was repor ted what defects, vacancies and doping with nitrogen atoms can increase the interaction force between the molecules and surfaces, besides to present a low level of toxicity. Based in these informations was used the density functional theory (DFT) to investigate the influency of one semiconductor layer of nitrogenated holey graphene (C2N-h2D) under the Gaba, Glycine and Glutamate neurotransmitters amino acids. The results show what the non-covalent interactions and electrostatic govern the physical adsorption process between the monolayer of C2N-h2D and the NAAs. Furthermore, the results revealed what this physical adsorption is extremely stronger when compared with previous results for NAAs on pure graphene. From application point view, was demonstred what the charge redistribution can increase or decrease the electro nic resistivityon the surface of C2N-h2D, which can be an excellent resource for applying the structure C2N-h2D as a biosensor.